Geographical Variations in Elderly Disability in Taiwan - 莊坤洋(Kun-Yang Chuang); 莊媖智(Ying-Chih Chuang); 陳亮汝(Liang-Ju Chen); 吳淑瓊(Shwu Chong Wu) (The Journal of Nursing Research, 2008)
Inequality in health has long been a topic of discussion. The purpose of this research was to provide estimates of the proportions of elderly who had difficulties in activities of daily living in each of the 23 administrative areas of Taiwan, and to assess if there was geographical disparity in disability across areas. A nationally representative sample of 303,545 subjects was selected for interview. Among the subjects selected for interview, 239,861 completed the survey, a completion rate of about 80%. For the purpose of this research, only those aged 65 years or older were included (N = 114,873) in the analyses. Non-standardized and standardized prevalences of disability were presented for each of the 23 administrative areas in Taiwan, and geographical distribution of elderly disability was plotted. Results show that significant difference in disability prevalence exists among administrative districts, even after adjusting for age and sex structure of the population. Moreover, the extent of gender disparity also varied from one area to another. The western region, in general, had lower disability prevalence than the eastern region. Findings imply that since disability prevalence varied significantly across administrative areas, funding for long-term care should not be allocated based on the number of elderly population in an administrative area. Areas with high prevalence should identify reasons for their high prevalence rates and implement proper interventions.